ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI INOVASI TERAPI RELAKSASI BENSON PADA KLIEN GAGAL GINJAL KRONIS YANG MENGALAMI KECEMASAN DI KELURAHAN CIPULIR - Mutiara Zahira Fajri (2022)
Chronic kidney failure is a disease characterized by a decrease in kidney function in metabolic processes and maintaining electrolyte and fluid balance which can lead to accumulation of metabolic waste substances. One of the medical actions that can be done in patients with chronic kidney failure is hemodialysis. Hemodialysis will become a routine for patients with chronic kidney failure throughout their lives. Psychological problems can arise such as excessive fear, insomnia, worry, irritability, difficulty concentrating, doubt, feeling low in self-esteem, and anxiety or anxiety. Management to overcome anxiety in patients with chronic kidney failure with non-pharmacological therapies that can be applied, one of which is Benson relaxation therapy. The purpose of this scientific work is to determine the effect of Benson's relaxation therapy in reducing anxiety in chronic kidney failure patients. After Benson relaxation therapy in managed patients and a resume, it was found that there was a decrease in anxiety levels from the category of severe anxiety to low anxiety in both clients